Advances in Cardiology in 2023 - Soufi-Taleb Bendiab, N.; N. Khedim; D. Kazi-Tani; M. Bensalah; A. Sari; S. Djafour (International Journal of Medical Science and Clinical Research Studies, 2024)
Cardiology continues to evolve from year to year with major advances in its different disciplines which we have summarized in this review by selecting the main chapters allowing us to improve our daily practice.